2017
DOI: 10.1007/s11606-017-4010-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pregnancy and Gender on Internal Medicine Resident Evaluations: A Retrospective Cohort Study

Abstract: A large number of residents experience pregnancy during residency. Mean peer evaluation scores were lower after pregnancy for female residents. Further study is needed to fully understand the mechanisms behind these findings, develop ways to optimize training throughout pregnancy, and explore any unconscious biases that may exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 21 publications
4
33
1
Order By: Relevance
“…Similarly, a retrospective cohort study of internal medicine residents revealed that performance evaluation scores of female residents decreased following pregnancy. 9 The same trend was not seen for male residents with pregnant partners. This trend is particularly salient given that women comprise a growing number of medical school graduates and resident physicians.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, a retrospective cohort study of internal medicine residents revealed that performance evaluation scores of female residents decreased following pregnancy. 9 The same trend was not seen for male residents with pregnant partners. This trend is particularly salient given that women comprise a growing number of medical school graduates and resident physicians.…”
Section: Resultsmentioning
confidence: 85%
“…In a previous singleinstitution report, internal medicine residents rated the performance of female peers in the postpartum period lower compared to their male peers who also became parents during residency. 9 Family medicine PDs also perceive a differential impact of parenting on performance in male and female residents (79.6% stated parenting had no impact on male residents compared to 70.4% reporting no effect on female residents; P=.006). Growing evidence suggests this trend exists across specialties.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the eight articles used in the PW workforce gender equity chat focused on a different topic (Table 1), including the core macroinequities of financial compensation (Compensation), 23 academic rank and leadership role promotion (Promotion), 2 and recognition awards (Awards). 24 Microinequity articles included in the chat focused on internal medicine attending and peer evaluations of residents who became new parents while in training (Pregnancy), 15 and gender differences in attending physician feedback to residents (Evaluation). 25 Three additional articles were included that focused on sexual harassment (Me Too), 26 metrics that can be used by medical societies to analyze gender equity (Metrics), 4 and well-being among trainees who feel judged on the basis of gender identity ( Judged).…”
Section: Resultsmentioning
confidence: 99%
“…14 Five days after meeting, summit attendees participated in a proof-of-concept study of the impact of social media postings on research dissemination. During this preliminary study, attendees posted comments and information about a pregnancyrelated workforce gender equity article by Krause et al titled ''Impact of Pregnancy and Gender on Internal Medicine Resident Evaluations: A Retrospective Cohort Study'' 15 on Twitter and Facebook. AS Oxentenko, the senior author of that article and coauthor of this study, looked at the effects of gender and pregnancy on the evaluation scores given to internal medicine residents between July 1, 2004 and June 30, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…1 The impact of pregnancy in residency extends beyond the female resident. This article mentions a study from 1983 in which resident colleagues were surveyed regarding their feelings toward their pregnant colleagues.…”
mentioning
confidence: 99%